Ectopic expression of OsMADS45 activates the upstream genes Hd3a and RFT1 at an early development stage causing early flowering in rice - Wang, Jiun-Da; Lo, Shuen-Fang; Li, Yan-Suan; Chen, Po-Ju; Lin, Shih-Yun; Ho, Teh-Yuan; Lin, Jenq-Horng; Chen, Liang-Jwu (Botanical studies, 2013)
Background The rice gene, OsMADS45 , which belongs to the MADS-box E class gene, participates in the regulation of floral development. Previous studies have revealed that ectopic expression of OsMADS45 induces early flowering and influences reduced plant height under short-day (SD) conditions. However, the regulation mechanism of OsMADS45 overexpression remains unknown. We introduce an OsMADS45 overexpression construct Ubi:OsMADS45 into TNG67 plants (an Hd1 ( Heading date 1 ) and Ehd1 ( Early heading date 1 ) defective rice cultivar grown in Taiwan), and we analyzed the expression patterns of various floral regulators to understand the regulation pathways affected by OsMADS45 expression. Results The transgenic rice exhibit a heading date approximately 40 days earlier than that observed in TNG67 plants, and transgenic rice display small plant size and low grain yield. OsMADS45 overexpression did not alter the oscillating rhythm of the examined floral regulatory genes but advanced (by approximately 20 days) the up-regulate of two florigens, Hd3a ( Heading Date 3a ) and RFT1 ( RICE FLOWERING LOCUS T1 ) and suppressed the expression of Hd1 at the juvenile stage. The expression levels of OsMADS14 and OsMADS18 , which are two well-known reproductive phase transition markers, were also increased at early developmental stages and are believed to be the major regulators responsible for early flowering in OsMADS45 -overexpressing transgenic rice. OsMADS45 overexpression did not influence other floral regulator genes upstream of Hd1 and Ehd1 , such as OsGI (OsGIGANTEA) , Ehd2/Osld1/RID1 and OsMADS50 . Conclusion These results indicate that in transgenic rice, OsMADS45 overexpressing ectopically activates the upstream genes Hd3a and RFT1 at early development stage and up-regulates the expression of OsMADS14 and OsMADS18 , which induces early flowering.